Application of Click Chemistry Conditions for 5‐Bromo‐2′‐Deoxyuridine Determination Through Fenton and Related Reactions. Issue 1 (5th January 2015) - Cappella, Paolo; Pulici, Maurizio; Gasparri, Fabio
Abstract: Mixtures of ascorbate and copper used in certain click chemistry experimental conditions act as oxidizing agents, catalyzing the formation of reactive oxygen species through Fenton and related reactions. Hydroxyl radicals act as chemical nucleases, introducing DNA strand breaks that can be exploited for BrdU immunostaining in place of acid denaturation. This procedure is readily applicable to high content analysis and flow cytometry assays, and provides results comparable to click chemistry EdU cycloaddition and classical BrdU immunodetection. Importantly, this approach allows preservation of labile epitopes such as phosphoproteins. This unit describes an optimized method that successfully employs Fenton chemistry for simultaneous detection of phosphoproteins and BrdU in intact cells. © 2015 by John Wiley & Sons, Inc.